The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41477-020-0616-4
|View full text |Cite|
|
Sign up to set email alerts
|

Chlorophyll f synthesis by a super-rogue photosystem II complex

Abstract: Certain cyanobacteria synthesize chlorophyll (Chl) molecules (Chl d and Chl f) that absorb in the far-red region of the solar spectrum thereby extending the spectral range of photosynthetically active radiation 1,2. The synthesis and introduction of these far-red Chls into the photosynthetic apparatus of plants might improve the efficiency of oxygenic photosynthesis, especially in far-red enriched environments, such as in the lower regions of the canopy 3. Production of Chl f requires the ChlF subunit, also kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 44 publications
(37 reference statements)
0
47
0
Order By: Relevance
“…What is more, these structural and functional features, together with the ASR analysis (Supplementary Fig. S8 and S9) suggest that the atypical forms of D1, lacking ligands to the Mn 4 CaO 5 cluster, such as the chlorophyll f synthase [ 33 , 75 ], or the “rogue” or “sentinel” D1 [ 32 , 76 ], diverged from forms of D1 that were able to support water oxidation, but that could antedate the MRCA of Cyanobacteria [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…What is more, these structural and functional features, together with the ASR analysis (Supplementary Fig. S8 and S9) suggest that the atypical forms of D1, lacking ligands to the Mn 4 CaO 5 cluster, such as the chlorophyll f synthase [ 33 , 75 ], or the “rogue” or “sentinel” D1 [ 32 , 76 ], diverged from forms of D1 that were able to support water oxidation, but that could antedate the MRCA of Cyanobacteria [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…It would be difficult to reconcile these unique structural and genetic features with a scenario in which PSII evolved water oxidation at a late stage, or starting as a purple anoxygenic type II RC, once the heterodimerization process was well underway or completed, or in the absence of core antenna domains, given that these interact directly with the electron donor side of PSII, in a manner strikingly similar to that of the homodimeric type I RC of the Firmicutes [19]. What is more, these structural and functional features also suggest that the atypical forms of D1, lacking ligands to the Mn4CaO5 cluster, such as the so-called chlorophyll f synthase [32, 71], or the so-called “rogue” or “sentinel” D1 [31, 72], diverged from forms of D1 that were able to support water oxidation. Even if they originated from early duplications that could have antedated the MRCA of Cyanobacteria [2] and as additionally supported by ASR analysis (Supplementary Figure S9 and S10).…”
Section: Discussionmentioning
confidence: 99%
“…D2 subunit of PSII to synthesize Chl f [28]. Remarkably, it was shown that, by engineering chimeric D1/ChlF proteins in Synechocystis sp.…”
Section: Co2mentioning
confidence: 99%
“…Remarkably, it was shown that, by engineering chimeric D1/ChlF proteins in Synechocystis sp. PCC 6803, which natively does not harbor Chl f pigments, the engineered strain could synthesize Chl f pigments [28]. The chimera strategy could potentially be interesting to enable Chl f synthesis in microalgae.…”
Section: Co2mentioning
confidence: 99%